Memories of the future: reception studies on Chinese science-fiction cinema, 1979-2016 - Lin, Tian-Ze (2019)
This thesis explores the history of the reception of science-fiction film in China from 1979 to 2016. It asks how Chinese audience received this genre in film discourse and in the industry and aims to address the research gap between the complexity of the construction of genre as a multi-dimensional process and the historically specific nature of the construction of Chinese science fiction as a category. The project focuses on three different contexts of reception history: Hollywood science-fiction film, domestic science-fiction film and literature-as-canon reception strategy in China. These contexts are used to outline the different texts relevant to the ‘horizon of expectation’ from reception theory. In exploring how Chinese film discourse and the Chinese film industry received science fiction as a genre, this project aims to interpret the integrated circulation of reception history of science-fiction films in China in a specific Chinese social and historical context. Overall, it argues that the literature-as-canon strategy was a crucial solution for genrification in the Chinese science-fiction film field from 1979 to 2016.